Measured Effect of Low-Height Solid Safety Barriers on Heavy Truck Noise. Issue 1 (January 2023) - Sperry, Benjamin R.; Rochat, Judith L.; Cubick, Karel L.; Khoury, Issam
Low-height solid safety barriers (SSBs) are constructed along highways where an adequate clear zone cannot be provided between the highway and an important roadside feature. Where a roadside SSB is a permanent installation, it is possible that it also provides noise reduction benefits. Highway traffic noise sources that could be shielded by a low-height SSB include tire–pavement noise and any other noise originating close to the pavement surface, such as a low exhaust on a heavy truck. This paper reports the findings of a study examining how heavy truck noise is shielded by low-height roadside SSBs. Measurements of the maximum sound level (Lmax) of individual heavy truck pass-by events at two representative locations in Ohio were obtained at a position where a low-height SSB was present as well as at a nearby unshielded position. The results indicated that a perceptible reduction in the pass-by event Lmax (between 3 and 5 dBA) was realized for locations behind the SSBs. Variations in the measured noise reduction were associated with the line-of-sight shielding between various truck noise sources and the receiver positions. For events in which the exhaust source was shielded by the SSB, the measured noise reductions were higher at the site with the 42-in. tall SSB, although there was no difference for the site with the shorter (32-in.) SSB. It is recommended that analysts consider the potential for noise reduction associated with low-height SSBs in locations where such barriers are expected to be permanent.